Health‐related quality of life in parents of pediatric solid organ transplant recipients in Japan. (5th February 2015) - Kikuchi, Ryota; Ono, Minoru; Kinugawa, Koichiro; Endo, Miyoko; Mizuta, Koichi; Urahashi, Taizen; Ihara, Yoshiyuki; Yoshida, Sachiyo; Ito, Shuichi; Kamibeppu, Kiyoko
Abstract: Few studies have examined HRQOL in pediatric Tx recipients' parents. This study investigated HRQOL in these parents and relationships between HRQOL and perceived burden of nurturing, family functioning, and social support. Self‐report anonymous questionnaires and a survey of medical records were completed between September and December 2013. The SF‐36v2, which evaluates physical, psychological, and social health, was used to measure HRQOL. While values for physical and psychological health were higher than standard values (Cohen's d  = 0.34 and 0.17, respectively), social health scores were lower ( d  = 0.21). "Parental consultation unrelated to donation" (standardized partial regression coefficient: β = −0.52) was associated with physical health. "Family functioning" and "Commuting time between home and primary follow‐up hospital" (β = 0.57 and −0.31) were related to psychological health. "Total score for perceived burden of nurturing" (β = −0.31) was related to social health. Regarding parental HRQOL, while physical and psychological health was favorable, social health was impaired. In clinical practice, interventions targeting parents' physical conditions and facilitation of community and family understanding and support to share recipients' nurturing are important in improving parental HRQOL.